LEGAL STUDY ABOUT DEMOTION OF THE INDONESIAN NATIONAL ARMY AND POLICE IN THE DIRECTOR OF SEA TRANSPORTATION, THE MINISTRY OF TRANSPORTATION OF THE REPUBLIC OF INDONESIA - Junaedi Junaedi (Fakultas Hukum Universitas Komputer Indonesia, 2019)
Government in a country is one element or component in the formation of a good state. The realization of good governance is when there is a synergy between the private sector, the people and the government as a facilitator, which is carried out in a transparent, participatory, accountable and democratic manner. The process of achieving a country with good governance requires tools in bringing components of government policies or regulations to the realization of national objectives. The government apparatus is the government apparatus, namely: Indonesian National Army (TNI), Indonesian National Police (POLRI) and Civil Servants (PNS). The challenge faced by the government in the field of human resources apparatus as the main pillar of the administration of government is the challenge of being able to develop a human resource planning system (HR) of the government apparatus in accordance with the results of structuring institutional structures and devices. The consequence is the formation of discipline, ethics and morale at the executive level, namely: the Indonesian National Army (TNI), the Republic of Indonesia National Police (POLRI), and Civil Servants (PNS) aimed at increasing work productivity and demands on the realization of a corrupt government apparatus. , Collusion, Nepotism (KKN), and more professional. Based on the above background, the problem formulation in this paper is the legal study of the demotion of the TNI and Polri in the ranks of the Director General of Sea Transportation at the Ministry of Transportation of the Republic of Indonesia. The purpose of the study was to study and analyze the demotion of the TNI and Polri in the ranks of the Director General of Sea Transportation at the Ministry of Transportation of the Republic of Indonesia. Keywords. Demotion, Indonesian National Army/Indonesian National Police, Directorate General of Sea Transportation.